Excellent dielectric properties of PVDF-based composites filled with carbonized PAN/PEG copolymer fibers. (August 2016) - Guo, Qikai; Xue, Qingzhong; Wu, Tiantian; Pan, Xinglong; Zhang, Jianqiang; Li, Xiaofang; Zhu, Lei
Abstract: Weak interfacial bonding between carbon materials and polymer matrix impedes the formation of homogeneous composites, challenging to the enhancement of dielectric properties of such systems. In this work, we designed novel carbonized polyacrylonitrile/polyethylene glycol copolymer fibers (CPCFs) and then used them as fillers to enhance the dielectric properties of poly(vinylidene fluoride) (PVDF)-based composites. These CPCFs are rich in nitrogen (8.55%) and oxygen (3.94%) atoms on the surface of them. The results of molecular dynamic (MD) simulations indicate that the existence of these atoms significantly increase the interaction energy between CPCFs and PVDF matrix from −45.13 kcal/mol to −62.22 kcal/mol, which promotes the intercalation of conductive CPCFs into insulated PVDF matrix to form ultrathin microcapacitors. As a result, the largest dielectric constant of CPCFs/PVDF composites can reach 1583 (1 kHz), which is about 150 times higher than that of pure PVDF.